SISTEM INFORMASI MANAJEMEN PEMASARAN, PENJUALAN DAN DISTRIBUSI PRODUK CCTV (STUDI KASUS : TOKO KARYA JAYA SECURITY) - kiki rezeki; suidah suidah (Jurnal Teknologi dan Sistem Informasi, 2020)
Toko Karya Jaya Security is a company engaged in the sale of CCTV complete with Indoor or Outdoor Cameras, Monitors, DVR, Cables, Seagate Hard Drives, Power Supply, BNC Connectors and DC Connectors, Spare Parts, Fingerprint, Running Text and Video Tron. In the business of selling CCTV, Toko Jaya Security has not used technology as a sales or promotion medium to expand the product marketing process. For now, the business process carried out by Toko Karya Jaya Security is still done manually both in promoting products, sales between customers who still come directly to the store to order or buy CCTV products, and record transactions that are done manually. The purpose of this research is to design and build a CCTV Product Marketing, Sales and Distribution Management Information System that is used to help Toko Karya Jaya Security in expanding marketing and increasing sales of CCTV products, to making reports quickly and accurately. Data collection techniques used in this study are interviews, literature review and documentation. The data source was obtained from the head of Toko Karya Jaya Security. Marketing, Sales and Distribution Management Information System for web-based CCTV products is built using programming languages such as PHP and HTML. Database using MYSQL. The interface design is made using the Mockplus application. This system is tested using ISO 25010. This measurement is based on 6 main characteristics of ISO 25010, namely Functional Suitability, Reliability, Performance Efficiency, Usability, Maintainability and Portability. From the calculations carried out using the Likert scale, the result is 83.86%. So it can be concluded that the design of this system is declared very good to use and feasible to implement.